2017
DOI: 10.26458/1746
|View full text |Cite
|
Sign up to set email alerts
|

Two Criteria for Good Measurements in Research: Validity and Reliability

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
273
0
22

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 450 publications
(408 citation statements)
references
References 43 publications
5
273
0
22
Order By: Relevance
“…A validity test is performed using predictive validity, with reference to Mohajan (2017). He suggested that this test suits applied research.…”
Section: Validity and Reliability Of The Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…A validity test is performed using predictive validity, with reference to Mohajan (2017). He suggested that this test suits applied research.…”
Section: Validity and Reliability Of The Modelmentioning
confidence: 99%
“…A higher correlation between the criterion and the predictor indicates that the predictive validity is greater. According to Taherdoost (2016), the minimum recommended value for the valid items' loading is above 0.4, but Mohajan (2017) said that items with a loading between 3.0 and 0.6 are accepted as valid items. The decision about validity in this study refers to Mohajan (2017).…”
Section: Validity and Reliability Of The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A. Hatch identifies five research paradigms: positivist, post-positivist, constructivist, critical/feminist, and poststructuralist; and poses ontological, epistemological, and methodological questions for each [Hatch, 2002]. In a review paper Haradhan Kumar Mohajan has discussed reliability and validity of a good research that increase transparency, and decrease opportunities to insert researcher bias in qualitative research [Mohajan, 2017].…”
Section: Literature Reviewmentioning
confidence: 99%